2017
DOI: 10.1186/s40851-017-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

Group-housed females promote production of asexual ootheca in American cockroaches

Abstract: BackgroundFacultative parthenogenesis, seen in many animal phyla, is a reproductive strategy in which females are able to generate offspring when mating partners are unavailable. In some subsocial and eusocial insects, parthenogenesis is often more prevalent than sexual reproduction. However, little is known about how social cooperation is linked to the promotion of parthenogenesis. The domiciliary cockroach Periplaneta americana is well-suited to addressing this issue as this species belongs to the superfamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…However, the difference observed in G. lenticularis oothecae (unhatched and hatched and unfertilized) with regard to the number of eggs and length of the oothecae could indicate that these females would rather conserve valuable resources, instead of producing unfertilized oothecae which do not produce offspring. In contrast to this, a recent study [48] indicated that the length of the ootheca of a cockroach species (Periplaneta americana) Linnaeus 1758 (Blattodea: Blattidae), was not influenced by the fertility of the oothecae. Although P. americana can also reproduce through parthenogenesis, it is highly likely that females would not invest valuable resources into formation of oothecae if it produces no genetically diverse offspring.…”
Section: Biology Of Galepsus Lenticularismentioning
confidence: 76%
“…However, the difference observed in G. lenticularis oothecae (unhatched and hatched and unfertilized) with regard to the number of eggs and length of the oothecae could indicate that these females would rather conserve valuable resources, instead of producing unfertilized oothecae which do not produce offspring. In contrast to this, a recent study [48] indicated that the length of the ootheca of a cockroach species (Periplaneta americana) Linnaeus 1758 (Blattodea: Blattidae), was not influenced by the fertility of the oothecae. Although P. americana can also reproduce through parthenogenesis, it is highly likely that females would not invest valuable resources into formation of oothecae if it produces no genetically diverse offspring.…”
Section: Biology Of Galepsus Lenticularismentioning
confidence: 76%
“…We first investigated whether female adults of P. americana can reproduce parthenogenetically by individually rearing female nymphs from the laboratory colony. As previously reported (Takahashi, ; Roth & Willis, ; Xian, ; Katoh et al ., ), many of the virgin female adults (17 out of 23 adults, 73.9%) produced oothecae without mating.…”
Section: Resultsmentioning
confidence: 99%
“…Although the hatchability of parthenogenetic nymphs was low, we found that, once hatched, most of parthenogenetic nymphs grew well, without apparent abnormalities, regardless of the extremely low levels of genetic heterozygosity expected among them. Indeed, a recent study showed that the parthenogenetic offspring of P. americana are fertile and can produce offspring via thelytoky; a "female-only" parthenogenetic colony has been maintained in this manner for approximately 3 years (approximately six generations) (Katoh et al, 2017). This suggests that P. americana can potentially reproduce almost normally without sexual reproduction if recessive deleterious alleles are purged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations